A comprehensive review of challenges in oral drug delivery systems and recent advancements in innovative design strategies - Ying, Hui Loke; Jayakrishnan, Achuth; Mod Razif, Muhammad Redza Fahmi; Kar, Ming Yee; Phei, Er Kee; Bey, Hing Goh; Helal Uddin, A.B.M.; Lakshminarayanan, Vijayakumar; Kai, Bin Liew (Bentham Science Publishers, 2025)
The oral route of drug administration is often preferred by patients and healthcare providers due to its convenience, ease of use, non-invasiveness, and patient acceptance. However, traditional oral dosage forms have several limitations, including low bioavailability, limited drug loading capacity, and stability and storage issues, particularly with solutions and suspensions. Over the years, researchers have dedicated considerable effort to developing novel oral drug delivery systems to overcome these limitations. This review discusses various challenges associated with oral drug delivery systems, including biological, pharmaceutical, and physicochemical barriers. It also explores common delivery approaches, such as gastroretentive drug delivery, small intestine drug delivery, and colon-targeting drug delivery systems. Additionally, numerous strategies aimed at improving oral drug delivery efficiency are reviewed, including solid dispersion, absorption enhancers, lipid- based formulations, nanoparticles, polymer-based nanocarriers, liposomal formulations, microencapsulation and micellar formulations. Furthermore, innovative approaches like orally disintegrating tablets (ODT), orally disintegrating films (ODF), layered tablets, micro particulates, self-nano emulsifying formulations (SNEF), and controlled release dosage forms are explored for their potential in enhancing oral drug delivery efficiency and promoting patients’ compliance. Overall, this review highlights significant progress in addressing challenges in the pharmaceutical industry and clinical settings, offering novel approaches for the development of effective oral drug delivery systems.